2012
DOI: 10.1001/archoto.2012.1110
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapeutic Management of Cervical Lymph Node Metastases From an Unknown Primary Site

Abstract: IPSI radiation therapy demonstrated excellent locoregional control with no adverse effect on disease-free survival or overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
61
0
9

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 21 publications
7
61
0
9
Order By: Relevance
“…Although HPV status was strongly associated with non-keratinizing tumor histology, as in other studies, it was not associated with year of diagnosis, cystic node presentation, tumor differentiation, or smoking status, in contrast to previous reports (25, 27, 34) . HPV expression was also associated with a non-significant trend toward improved PFS (p=0.15) and OS (p=0.06), analogous to those for HPV-positive squamous cell carcinoma of known oropharyngeal origin (11, 26, 30, 34, 35) .…”
Section: Discussionmentioning
confidence: 87%
“…Although HPV status was strongly associated with non-keratinizing tumor histology, as in other studies, it was not associated with year of diagnosis, cystic node presentation, tumor differentiation, or smoking status, in contrast to previous reports (25, 27, 34) . HPV expression was also associated with a non-significant trend toward improved PFS (p=0.15) and OS (p=0.06), analogous to those for HPV-positive squamous cell carcinoma of known oropharyngeal origin (11, 26, 30, 34, 35) .…”
Section: Discussionmentioning
confidence: 87%
“…Therefore some recommend removing the larynx and hypoharynx from the field. In addition, it has been shown that patients with CUP treated with ipsilateral radiotherapy compared to a more comprehensive radiotherapy did not demonstrate a worse locoregional control or overall survival [34]. The best radiotherapy plan for patients with CUP is however not universally agreed upon [35].…”
Section: Discussionmentioning
confidence: 99%
“…This might be altered in cases of human papillomavirus (HPV) positive tumors, in which patients do present with advanced neck disease (Mollenhauer et al, 2014). The rates of distant metastasis between CUP and HNSCC patients are comparable (Perkins et al, 2012). According to the literature, CUP patients demonstrate improved overall survival despite a more advanced nodal stage, a higher incidence of ECS, and more advanced age.…”
Section: Discussionmentioning
confidence: 90%